Perancangan Sistem Informasi Untuk Pencarian Apotik Dengan Menerapkan Metode Prototyping Berbasis Android - Rima Tamara Aldisa (Journal of Information System Research (JOSH), 2022)
A pharmacy is a shop where you mix and sell medicines based on doctor's prescriptions and sell medical items. The goals and interests of system users here are citizens or communities who are the main priority which is important to provide better services for the future, system user satisfaction is needed to provide maximum service. With the creation of this system, which aims for users not to mind searching for the location of the nearest pharmacy, the prototyping method is here to design and develop the system. By designing a dispensary search system with this prototyping method so that the user system can immediately search for the nearest pharmacy, purchase drugs and there are pharmacies that can be ordered online and users do not have to come directly to the agency or to the pharmacy.